Bulgarian tourism and the problem of poverty alleviation in Bulgaria - Preslav Mihaylov Dimitrov; Rouska Kraseta; Boiko Dimitrov (Tourism & Management Studies)
The present research paper summarizes the results from a broader research on the topic “Bulgarian tourism and the problem of poverty in Bulgaria” commissioned by the German Foundation “Fridrich Ebert”, Sofia Bureau in 2014. Here, a more detailed literature review has been added to the one of the original research with the aim to follow the scientific discussion on this issue in the Bulgarian society for more than a century and to step on the more recent publications existing worldwide. The study examines the question about the ability of Bulgarian tourism to solve the problems with the widespread poverty in Bulgaria in the context of the two main issues such as: (i) the degree of association (in terms of Pearson’s Product-moment coefficients) of the Bulgarian tourism with the economic performance of the EU tourism emitting economies, and whether this association in particular contributes for “transmission of poverty”, and (ii) what will be the estimated volume of the average month salary of the employees on labor contracts in Bulgarian tourism for the next ten years by the HoltWinters exponential smoothing method. These two sub-questions, these two issues, have been chosen deliberately as the usual excuse of the representatives of the Bulgarian tourism industry for the much weaker results in comparison to the neighboring competing countries is that the tourists who come usually to Bulgaria from Western Europe are poorer. Another reason for the above posed questions is the contentiously repeated in the Bulgarian society “mantra” that the tourism sector in the country will grow on its own without any need of government support and direction and it will lead to a steady increase in the disposable incomes of the employed personnel. Although this claim might have appeared true for the end of the 1990s, the monthly level of salaries in tourism lags significantly behind many other service sectors in Bulgaria.